Indoor and Outdoor Gamma Dose Rate Exposure Levels in Major Commercial Building Materials Distribution Outlets in Jos, Plateau State-Nigeria - Jwanbot, D.I.; Izam, M.M.; Nyam, G.G.; Yusuf, M. (Asian Review of Environmental and Earth Sciences, 2014)
Certain types of building materials are known to be radioactive. Exposures to indoor and outdoor radiation like exposure to any other type of ionizing radiation result in critical health challenges. The measurements of the indoor and outdoor gamma dose rate exposure levels of various types of building materials in the major commercial building materials distribution outlets in Jos Plateau was carried-out. A total number of 56 shops where building materials are sold were surveyed using gamma-scout (model GS2 with serial number A20). The range of the radiation levels were: (0.258 - 0.264) mSv/yr and (0.218 - 0.226) mSv/yr for floor titles indoor and outdoor respective, (0.226 – 0.25 –0.250) mSv/yr and (0.210 - 0.214) mSv/yr for PVC ceiling indoor and outdoor respectively. The average total annual effective doses due to outdoor and indoor gamma exposures were 1.80mSv (floor tiles) and 1.64mSv (wall tiles) while for wash hand basin was 1.69mSv/yr, white cement and PVC pipes materials recorded the lowest annual effective dose amongst all the others, which is above 1mSv/yr (the acceptable limit for the general public). Hence these could pose some health hazards to the occupants of these store/shops.